Influence of Vinyl Acetate-Based and Epoxy-Based Compatibilizers on the Design of TPS/PBAT and TPS/PBAT/PBSA Films - Cristina Martín-Poyo; Josep P. Cerisuelo-Ferriols; Jose D. Badia-Valiente (Applied Sciences)
The study investigated the effect of Vinnex® (vinyl acetate polymer) and Joncryl® (epoxy-based copolymer) as compatibilizers on the mechanical properties of thermoplastic starch (TPS) and polybutylene adipate-co-terephthalate (PBAT) and polybutylene succinate-co-adipate (PBSA) films. Due to TPS’s hydrophilicity and brittleness, blending it with biodegradable polyesters like PBAT enhances its properties but may introduce compatibility challenges. This research evaluated three formulations (TPS/PBAT with Vinnex, TPS/PBAT with Joncryl, and TPS/PBAT with both additives) along with the inclusion of a polybutadiene succinate-co-adipate (PBSA) matrix to further improve performance. Mechanical testing (tensile strength, elongation at break, Young’s modulus) reveals that Vinnex and Joncryl enhance plasticization and polymer compatibility, positively impacting TPS/PBAT’s mechanical properties. The introduction of the PBSA matrix further improves tensile strength and elongation. Scanning electron microscopy (SEM) confirms better additive dispersion and interfacial adhesion within the blend. Complementary analysis includes melt flow index, melt density, DSC, and TGA, providing a comprehensive understanding of how these additives optimize TPS/PBAT compounds for sustainable applications. Mechanically, the compatibilized blends showed improved performance: Vinnex mainly enhanced stiffness, Joncryl primarily improved elongation, and a synergistic effect was observed with their combination.